Presence of condyloma lata in children with syphilis - Moreira-Silva, Sandra F; Frauches, Diana O; Prebianchi, Patricia A; Riccio, Claudia S B; Andreata, Grasielly R; Oliveira, Clarissa M; Emerich, Paulo Sérgio; Lima, Ana Paula NB (Brazilian Journal of Sexually Transmitted Diseases, 2006)
ntroduction: sexually transmitted diseases are a real epidemic and Syphilis has been historically provoking terrible harm; perhaps as much harm asaids. Objective:present three cases of syphilis in children, with initial clinical manifestation caused by condyloma lata. Method:case report extrac-ted from children’s medical handbooks at Hospital Infantil Nossa Senhora da Gloria. Case 1: L, nine years old, male, lesion at anal region suggestingcondyloma lata. Sexual molestation not present according to medical evaluation. VDRL 1:128, FTA-Abs IgG positive and IgM negative, normalliquor with non-reactive VDRL. Mother with VDRL 1:8, FTA-Abs IgG positive and IgM negative. Case 2: Gnb, five years old, female, Condyloma-tosa lesion at perianal region; sexual molestation suspicion not confirmed according to medical evaluation. VDRL, 1:256, normal liquor with non-reactive VDRL. Maternal sorology not undertaken. Case 3: K, four years old, female, aspects of Condylomatosa lesion at perianal region. Sexualmolestation not present according to medical evaluation. VDRL 1:256, FTA-Abs IgG reactive, normal liquor with non-reactive VDRL. Maternalsorology not undertaken. In all three cases, the classification of the disease, congenital or acquired, was not confirmed. Conclusion:there is not manyinformation on the medical literature regarding condyloma latain children. Hence, it becomes a challenge to pediatricians when diagnosing suchdisease, mainly because it may be confused with condyloma acuminado of papiloma virus – this being more frequent. Besides the importance ofrecognizing the condylomatosa lesion of syphilis, it is necessary to emphasize an adequate pre-natal assistance, aiming the reduction of congenitalsyphilis.